Effects of Regular Classes in Outdoor Education Settings: A Systematic Review on Students’ Learning, Social and Health Dimensions - Becker, Christoph; Lauterbach, Gabriele; Spengler, Sarah; Dettweiler, Ulrich; Mess, Filip (International journal of environmental research and public health, 2017)
Background: Participants in Outdoor Education Programmes (OEPs) presumably benefit from these programmes in terms of their social and personal development, academic achievement and physical activity (PA). The aim of this systematic review was to identify studies about regular compulsory school- and curriculum-based OEPs, to categorise and evaluate reported outcomes, to assess the methodological quality, and to discuss possible benefits for students. Methods: We searched online databases to identify English- and German-language peer-reviewed journal articles that reported any outcomes on a student level. Two independent reviewers screened studies identified for eligibility and assessed the methodological quality. Results: Thirteen studies were included for analysis. Most studies used a case-study design, the average number of participants was moderate (mean valued (M) = 62.17; standard deviation (SD) = 64.12), and the methodological quality was moderate on average for qualitative studies (M = 0.52; SD = 0.11), and low on average for quantitative studies (M = 0.18; SD = 0.42). Eight studies described outcomes in terms of social dimensions, seven studies in learning dimensions and four studies were subsumed under additional outcomes, i.e., PA and health. Eleven studies reported positive, one study positive as well as negative, and one study reported negative effects. PA and mental health as outcomes were underrepresented. Conclusion: Tendencies were detected that regular compulsory school- and curriculum-based OEPs can promote students in respect of social, academic, physical and psychological dimensions. Very little is known concerning students’ PA or mental health. We recommend conducting more quasi-experimental design and longitudinal studies with a greater number of participants, and a high methodological quality to further investigate these tendencies.